Redescription and first record in South America of Neogriphoneura timida Curran (Diptera, Lauxaniidae) - Mello, Ramon Luciano; Mahlmann, Thiago; Silva, Vera Cristina [UNESP] (FapUNIFESP (SciELO), 2017)
The genus Neogriphoneura Malloch, 1924 is currently composed of 11 species with New World distribution. Neogriphoneura timida Curran, 1942 is recorded for the first time in South America, with occurrences in Brazil, Colombia and Trinidad and Tobago; and new Central American records are presented: Belize, Honduras and Mexico. Here we redescribe the species and present, for the first time, illustrations of the male terminalia and female spermathecae, and discuss the main diagnostic characteristics of external morphology. A brief discussion about the postcopulatory sexual selection in this species is proposed based on morphology of the spermathecae.
Keywords: Distribution; Schizophora; Sperm competition; Spermathecae; Spermatozoa